Development and characterization of wheat breads with chestnut flour - Gonzaga, Marta (2015)
A new type of bread, was prepared with wheat and chestnut flours, without the addition of any conservatives. Several experiences were also done to find the most appropriate proportion of chestnut flour. The particle size of different fractions of chestnut flour did not influence the flour water absorption, and they presented similar protein content. The farinographic experiences showed that the water absorption of wheat flour with 10% of chestnut was similar to the wheat flours. The extensographic analysis revealed that 45 minutes is the optimum fermentation time, with higher resistance to extension. The addition of chestnut flour increased the dough stability. The optimized product was characterized considering the rheological, physical-chemical and sensorial properties. The breads presented low moisture but a considerable water activity. Bread density decreased and their dimensions increase. The breads were quite white, and during storage the color parameters changes differently. The chestnut flour clearly increased the number of alveolus, but the total area was similar to the wheat breads. The elasticity of breads did not vary significantly, but increase after the third day of storage. The addition of chestnut flour influenced significantly the appearance of bread, and this bread was sweeter and presented a higher score in the global appreciation.